Images from childhood : an exploration of scripted television programme for Singaporean children from the 2000s - Tan, Eunice Hui Lin (Nanyang Technological University, 2022)
With Singapore gaining its independence in 1965, then prime minister Lee Kuan Yew has always had anxiety regarding potential Western influences invading Singapore’s shore. The Singapore government when creating mass media broadcasting stations have thus constantly been wary of the spread of media that boasted Western values. In Singapore’s short broadcasting history is an even shorter history of public, free-to-air children’s broadcasting. With the launch of every new public children’s broadcasting network such as Kids Central in the early 2000s and Okto in 2008, Mediacorp always insisted on keeping the media broadcasted on such channels to locally produced content. This thesis tracks the rise and fall of such children’s broadcasting channels, deep analysis of what local even is and the values meant to be spread through mass media, in addition to how the rise of the digital age has caused a disconnect between children across different generations.